Assessing couples' preferences for fresh or frozen embryo transfer: a discrete choice experiment. Issue 11 (22nd September 2021) - Abdulrahim, Baydaa; Scotland, Graham; Bhattacharya, Siladitya; Maheshwari, Abha
Abstract: STUDY QUESTION: What are couples' preferences for fresh embryo transfer versus freezing of all embryos followed by frozen embryo transfer and the associated clinical outcomes that may differentiate them? SUMMARY ANSWER: Couples' preferences are driven by anticipated chances of live birth, miscarriage, neonatal complications, and costs but not by the differences in the treatment process (including delay of embryo transfer linked to frozen embryo transfer and risk of ovarian hyperstimulation syndrome (OHSS) associated with fresh embryo transfer). WHAT IS KNOWN ALREADY: A policy of freezing all embryos followed by transfer of frozen embryos results in livebirth rates which are similar to or higher than those following the transfer of fresh embryos while reducing the risk of OHSS and small for gestational age babies: it can, however, increase the risk of pre-eclampsia and large for gestational age offspring. Hence, the controversy continues over whether to do fresh embryo transfer or freeze all embryos followed by frozen embryo transfer. STUDY DESIGN, SIZE, DURATION: We used a discrete choice experiment (DCE) technique to survey infertile couples between August 2018 and January 2019. PARTICIPANTS/MATERIALS, SETTING, METHODS: We asked IVF naïve couples attending a tertiary referral centre to independently complete a questionnaire with nine hypothetical choice tasks between fresh and frozen embryo transfer. The alternatives varied across the choice occurrences on several attributes including efficacy (live birth rate), safety (miscarriage rate, neonatal complication rate), and cost of treatment. We assumed that a freeze-all strategy prolonged treatment but reduced the risk of OHSS. An error components mixed logit model was used to estimate the relative value (utility) that couples placed on the alternative treatment approaches and the attributes used to describe them. Willingness to pay and marginal rates of substitution between the non-cost attributes were calculated. A total of 360 individual questionnaires were given to 180 couples who fulfilled the inclusion criteria, of which 212 were completed and returned Our study population included 3 same sex couples (2 females and 1 male) and 101 heterosexual couples. Four questionnaires were filled by one partner only. The response rate was 58.8%. MAIN RESULTS AND THE ROLE OF CHANCE: Couples preferred both fresh and frozen embryo transfer (odds ratio 27.93 and 28.06, respectively) compared with no IVF treatment, with no strong preference for fresh over frozen. Couples strongly preferred any IVF technique that offered an increase in live birth rates by 5% ( P = 0.006) and 15% ( P < 0.0001), reduced miscarriage by 18% ( P < 0.0001) and diminished neonatal complications by 10% ( P < 0.0001). Respondents were willing to pay an additional £2451 (95% CI 604 − 4299) and £761 (95% CI 5056–9265) for a 5 and 15% increase in the chance of live birth, respectively, regardless of whether this involved fresh or frozen embryos. They required compensation of £5230 (95% CI 3320 − 7141) and £13 245 (95% CI 10 110–16 380) to accept a 10 and 25% increase in the risk of neonatal complications, respectively ( P < 0.001). Results indicated that couples would be willing to accept a 1.26% (95% CI 1.001 − 1.706) reduction in the live birth rate for a 1% reduction in the risk of neonatal complications per live birth. Older couples appeared to place less emphasis on the risk of neonatal complications than younger couples. LIMITATIONS, REASONS FOR CAUTION: DCEs can elicit intentions which may not reflect actual behaviour. The external validity of this study is limited by the fact that it was conducted in a single centre with generous public funding for IVF. We cannot rule out the potential for selection or responder bias. WIDER IMPLICATIONS OF THE FINDINGS: If a strategy of freeze all was to be implemented it would appear to be acceptable to patients, if either success rates can be improved or neonatal complications reduced. Live birth rates, neonatal complication rates, miscarriage rates, and cost are more likely to drive their preferences than a slight delay in the treatment process. The results of this study have important implications for future economic evaluations of IVF, as they suggest that the appropriate balance needs to be struck between success and safety. A holistic approach incorporating patient preferences for expected clinical outcomes and risks should be taken into consideration for individualized care. STUDY FUNDING/COMPETING INTEREST(S): No external funding was sought for this study. A.M. is the chief investigator of the randomized controlled trial 'Freeze all'. S.B. is an Editor in Chief of Human Reproduction Open . The other co-authors have no conflicts of interest to declare. Graham Scotland reports non-financial support from Merck KGaA, Darmstadt, Germany, outside the submitted work. TRIAL REGISTRATION NUMBER: N/A.